FINANCIAL FUNDAMENTALS FOR DEVELOPING THE INNOVATION POTENTIAL - I. N. Molchanov; N. P. Molchanova (Финансы: теория и практика)
Defining the content and structure of the research (innovation) potential as part of the total economic potential of the national economy is a debatable issue. A careful study of different definitions allowed us to formulate a synthetic definition of the notion “scientific potential” as a set of resource (tangible) and intellectual (intangible) assets needed for developing innovation in various spheres of economic activities. The basic method applied for studying the research (innovation) potential was a systematic approach. The data presented in the information system of the state statistics were used as a basis for evaluation. In the conditions of intensification and structural modernization of production, the key task in developing the innovation potential is to attract investors who possess financial resources and can acquire advanced technologies to implement innovative projects. Innovative activity of organizations is directly linked to financing of R & D. In Russia, the main part of research spending is covered by the government while in the developed countries, the private sector takes a significant role in financing scientific research. The analysis carried out by the authors proves that there is a variety of ways of attracting financial resources in the field of science.